Peningkatan Kinerja Guru Melalui Penguatan Budaya Organisasi dan Komunikasi Interpersonal - Endang Sulistyaniningsih; Natalia Tri Astuti; Nandang Hidayat (SAP (Susunan Artikel Pendidikan), 2022)
Basically every school that is in its environment will always compete with other schools in achieving a goal, therefore to realize a goal of the organization and to win a healthy competition, a vision and mission is indeed needed as a work guideline in achieving its goals. The aims of this study to determine and analyze the extent to which organizational culture and interpersonal communication have an effect on improving teacher performance at SMA Negeri 28 Jakarta. The research method used was a descriptive survey conducted on teachers in December 2021-February 2022. The sample was taken using a simple random sampling technique of 22 teachers. The instrument used in the form of a questionnaire compiled by the researcher. The data was analyzed first by testing the data analysis requirements, namely normality test, regression linearity test and multicollinearity test. After the test data requirements were met, a differential analysis was carried out for testing the research hypothesis using correlation analysis and multiple regression techniques. From the results of the study it was found that: (1) there was a positive and significant influence of organizational culture and interpersonal communication together on improving teacher performance; (2) there was a positive and significant influence of organizational culture on improving teacher performance; (3) there was a positive and significant effect of interpersonal communication on teacher performance.